Conservative management of acute perforated diverticulitis: A systematic review. Issue 2 (16th February 2020) - Chua, Terence C.; Jeyakumar, Arunan; Ip, Julian C.Y.; Yuide, Peter J.; Burstow, Matthew J.
Abstract : Objective: Acute perforated diverticulitis is frequently observed and spans a spectrum in the severity of its presentation. Emergency surgery is required in patients with generalized peritonitis; however, a large proportion of patients are clinically stable with localized peritonitis. This article aimed to examine this specific group of patients by reviewing the outcomes of their conservative management. Methods: A systematic literature search was performed on the MEDLINE and PubMed databases. The management outcomes of patients undergoing non‐operative treatment for acute perforated diverticulitis were synthesized and tabulated. Results: Of 479 patients, 407 (85%) were successfully managed non‐operatively. In total 70 (14.6%) patients failed non‐operative treatment and underwent operative surgical management, and two (0.4%) died. Emergency surgery includes a Hartmann's operation (40%) and resection with anastomosis with or without stoma (24%), laparoscopic lavage (16%) and surgical drainage (20%). The success rate of conservative management was 94.0% and 71.4% for patients with pericolic and distant free air, respectively. Treatment failure was associated with a high volume of free air, distant free air and the presence of abscess. Conclusions: Conservative management is safe and successful in patients with acute perforated diverticulitis without generalized peritonitis. The early recognition of patients who show clinical signs of persistent perforation is important to ensure the success of this strategy.